Embryonal Rhabdomyosarcoma: A Case Report - Mahbub, Muntasir; Mannan, Nabila; Shaheen, Md Mazharul; Chakraborti, Manash Ranjan; Shaifuddin, AKM; Kabir, Shahjahan; Murshed, KM Mamun; Hassan, Mahmudul; Ahmed, Khabiruddin (Bangladesh Journal of Otorhinolaryngology, 2016)
Rhabdomyosarcoma is the most common soft tissue sarcoma of childhood and adolescence. There are four histological types and among them the embryonic types are the most common. It can occur in any anatomic location, although when occurring in the head and neck region, it has an affinity to invade the cranial cavity. Patient was a 5 years old boy who was admitted with the complaints of pain and discharge from the ear, swelling on left side of the upper neck, and mastoid region and a fleshy mass protruding from the ear canal. The mass was confirmed to be Embryonal Rhabdomyosarcoma on histopathology. CT scan of the Head-Neck region, showed extension of the mass into infra-temporal fossa and in the mastoid antrum. After complete excision, the patient was referred to oncology deptt for consultation. The chemotherapy schedule comprised of Vincristine and Dactinomycine for 9-12 cycles. Otolaryngologists need to be aware of this rare condition as it may mimic the symptoms of CSOM or nasal polyp. And also long term followup is needed since recurrence can present several years after initial treatment. Bangladesh J Otorhinolaryngol; October 2015; 21(2): 127-131